ctga | |
=Cos2a | |
tg2a+ctga |
| sina | |||||||||||||||
L= | * | = | ||||||||||||||
| sina |
cosa | cosa*cos2a | |||||||||
= | = | = | ||||||||
| sina*sin2a+cosa*cos2a |
cosa*cos2a | cosa*cos2a | |||
= | = | = cos2a=P | ||
cos(2a−a) | cosa |
ctga | ctga*tga | 1 | |||||||||||||||||||
L= | = | = | = | ||||||||||||||||||
| tg2a*tga+1 |
|
cosa*cos2a | ||
= | = cos2a=P | |
cos(2a−a) |
2tga | 1 | |||
tg2a= | i ctga= | , tga≠0 | ||
1−tg2a | tga |
| tga | |||||||||||||||
L= | * | |||||||||||||||
| tga |
1 | 1−tg2a | cos2a−sin2a | ||||||||||
= | = | = | = cos2a=P | |||||||||
| 1+tg2a | cos2a+sin2a |